From Participatory to Lateral Surveillance: Municipal Apps as Platforms for Digital Informants - Volinz, Lior; Melgaço, Lucas; Steenhout, Iris (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
Municipal apps prompt citizens to report incidents of urban disorder and nuisance in a quick and simple manner directly from their mobile devices to the relevant municipal department. Presented as participatory surveillance tools, these apps allow local authorities to crowdsource information on the urban environment directly from citizens. However, these same platforms also enable individual citizens to anonymously report one another for minor criminal offences, such as vandalism, graffiti, public urination, parking violations, or illegal trash dumping. Focusing on FixMyStreet, a municipal app used in Brussels, Belgium, this paper draws on a content analysis of the FixMyStreet reports’ open database to explore how the introduction of participatory surveillance tools can open up spaces for lateral surveillance where citizens surveil each other. We delve into how municipal apps can contribute to the emergence of digital informants—and how this process risks (extralegal) vigilantism, ethnic profiling, privacy infringement, exacerbated neighbours’ feuds, or diminished social cohesion. We then explore the different social and political concerns emerging with the growth of lateral surveillance in urban spaces and make several propositions to ameliorate local authorities’ adoption and handling of municipal apps.